THE INFLUENCE OF POLITICAL FIGURES ON GOLKAR PARTY'S VICTORY IN THE 2024 LEGISLATIVE ELECTIONS IN NORTH SUMATRA PROVINCE - Fuad Putera Perdana Ginting; Ara Auza; Fernanda Putra Adela (OPINI: Journal of Communication and Social Science, 2025)
This study aims to analyze the influence of political figures on the victory of the Golongan Karya (Golkar) Party in the 2024 Legislative Election in North Sumatra Province. The study focuses on the role of Musa Rajekshah (Bang Ijeck) as the Chairperson of the Regional Leadership Council (DPD) of Golkar North Sumatra, who is considered successful in mobilizing public support through social capital, a positive public image, and effective political communication strategies. This research employs a quantitative method using a multiple linear regression approach, involving 400 respondents selected through a stratified purposive sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through validity, reliability, and classical assumption tests, followed by hypothesis testing. The results show that political figures have a positive and significant effect on voters’ decisions, with a coefficient value of 0.414, a t-value of 8.861, a significance level of 0.000, and a contribution of 61% (R² = 0.610). These findings confirm that local political figures can be a key factor in winning elections, even without support from national figures or the dominance of money politics practices. The practical implication of this study highlights the importance for political parties to maintain and develop the image of political figures who possess integrity, strong capacity, and emotional closeness to the community, supported by adaptive communication strategies tailored to different voter segments.